2016
DOI: 10.1128/jvi.03219-15
|View full text |Cite
|
Sign up to set email alerts
|

Entry Sites of Venezuelan and Western Equine Encephalitis Viruses in the Mouse Central Nervous System following Peripheral Infection

Abstract: Venezuelan and western equine encephalitis viruses (VEEV and WEEV; Alphavirus; Togaviridae) are mosquito-borne pathogens causing central nervous system (CNS) disease in humans and equids. Adult CD-1 mice also develop CNS disease after infection with VEEV and WEEV. Adult CD-1 mice infected by the intranasal (i.n.) route, showed that VEEV and WEEV enter the brain through olfactory sensory neurons (OSNs). In this study, we injected the mouse footpad with recombinant WEEV (McMillan) or VEEV (subtype IC strain 3908… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…Others have reported that VEEV can move in a retrograde manner up olfactory neurons crossing the cribriform plate and infecting glomeruli in the olfactory bulb, which could seed infection of the cortex and ultimately the hindbrain. Alternatively, virus could enter the brain directly during epithelial disruption at the choroid plexus or by crossing the BBB after moving via lymphatic drainage into the circulation (Phillips et al, 2016). We used in vivo 2P imaging of wild type and Ifit1 −/− mice to analyze the spatiotemporal distribution of virus following intranasal infection.…”
Section: Resultsmentioning
confidence: 99%
“…Others have reported that VEEV can move in a retrograde manner up olfactory neurons crossing the cribriform plate and infecting glomeruli in the olfactory bulb, which could seed infection of the cortex and ultimately the hindbrain. Alternatively, virus could enter the brain directly during epithelial disruption at the choroid plexus or by crossing the BBB after moving via lymphatic drainage into the circulation (Phillips et al, 2016). We used in vivo 2P imaging of wild type and Ifit1 −/− mice to analyze the spatiotemporal distribution of virus following intranasal infection.…”
Section: Resultsmentioning
confidence: 99%
“…The viral supernatants were checked using plaque assays. For the plaque assay, Vero cells were plated in 12-well plates at a density of 2.5 x 10 [5] cells/well and cultured in DMEM at 37.1°C, 5% CO 2 . After a 1h adsorption with a serially diluted virus solution, wells were covered with Eagle’s Minimum Essential Medium (Quality Biological 115–073-101) (without phenol red, supplemented with 10% FBS, non-essential amino acids, 1 mM sodium pyruvate, 2 mM L-glutamine, 20 U/ml of penicillin and 20 μg/ml of streptomycin) containing 0.6% agarose (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…EEEV-FL93-NLuc plasmid was obtained from Dr. William Klimstra (The University of Pittsburgh) and rescued as described (Sun et al, 2014). WEEV-McM-FLuc was constructed and generated as previously described (Phillips et al, 2016). All recombinant viruses were used without further passage after rescue.…”
Section: Methodsmentioning
confidence: 99%